Simian Virus 40 Mutants with Deletions at the 3′ End of the Early Region Are Defective in Adenovirus Helper Function - Cole, Charles N. (1979)
Coinfection of monkey cells with simian virus 40 (SV40) and adenovirus type 2 (Ad2) increased the Ad2 yield 1,000-fold over that obtained by Ad2 infection alone of monkey cells (A. S. Rabson, G. T. O'Conor, I. K. Berezesky, and F. J. Paul, Proc. Soc. Exp. Biol. Med. 116:187-190, 1964). The ability of viable mutants of SV40 that contain deletions at various sites in the viral DNA to enhance Ad2 growth in monkey cells was examined. Only those mutants with deletions near the 3′ end of the early region were deficient in providing this helper function. Mutants dl1265, lacking 39 base pairs at map position 0.18, and dl1263, lacking 33 base pairs at map position 0.20 (H. van Heuverswyn, C. Cole, P. Berg, and W. Fiers, J. Virol. 30:936-941, 1979), were approximately 4 and 30% as effective as wild-type SV40, respectively. The extent of enhancement of Ad2 yield depended on the multiplicity of infection by SV40, but not by Ad2 (at a multiplicity of infection of ≤50), as well as on the relative times of infection by Ad2 and SV40. Increasing the SV40 multiplicity of infection or infecting cells with SV40 wild type or mutants prior to Ad2 infection increased the Ad2 yield dramatically. The T antigens of wild-type SV40, dl1263, and dl1265 were examined. We attempt to correlate defects in helper function, alterations in the T antigen structure, and the DNA sequence of the mutants as determined by van Heuverswyn et al. (J. Virol. 30:936-941, 1979).